Primato ed episcopato: la Costituzione Apostolica Praedicate Evangelium nella scia del Concilio Vaticano II - Kouveglo, Émile (Apollinaris, 2022)
1. Introductory considerations: from the Second Vatican Council to the Praedicate Evangelium. 2. The Primacy, the Episcopate and "healthy decentralization". 3. The Primacy in a key which does not substitute but supports the mission of the episcopate. 4. The episcopate's contribution to the Roman Curia's mission. 5._Concluding remarks: What is expected of the episcopate today?